Targeted proteomics upon treatment with tofersen identifies novel response markers for superoxide dismutase 1-linked amyotrophic lateral sclerosis - Steffke, Christina; Baskar, Karthik; Bachhuber, Franziska; Wiesenfarth, Maximilian; Dorst, Johannes; Schuster, Joachim; Schöberl, Florian; Reilich, Peter; Regensburger, Martin; German, Alexander; Günther, René; Vidovic, Maximilian; et al. (Annals of neurology, 2025)
Objective Tofersen is the first effective and approved therapy for superoxide dismutase 1 (SOD1)-associated amyotrophic lateral sclerosis (ALS [SOD1-ALS]). Following treatment with tofersen, neurofilament levels in patients' cerebrospinal fluid (CSF) and serum seem to respond earlier than clinical parameters. This evidence prompted us to hypothesize that this novel treatment could provide an opportunity to identify additional biomarkers responsive to therapy in SOD1-ALS. Methods We investigated a panel of 120 neural, glial, and inflammatory markers in CSF and serum samples longitudinally collected from a total of 28 SOD1-ALS patients at baseline, and after 3, 6 and 12 months of treatment with tofersen, followed by validation with conventional methodology. Results We identified a set of proteins, including neurofilament light chain, neurofilament heavy chain, amyloid-beta 1-40 and amyloid-beta 1-42, neuropeptide Y (NPY), and ubiquitin C-terminal hydrolase L1 (UCHL1), whose CSF levels both differed between SOD1-ALS and the control group, and were responsive to tofersen at 3 and 6 months after treatment initiation. Another group of markers, including the neuropentraxin (NPTX) family members NPTX1, NPTX2 and NPTXR, did not separate untreated SOD1-ALS from controls, but was responsive to tofersen. At 12 months on tofersen the levels of neurofilament light chain, neurofilament heavy chain, NPTX1, NPTX2, and NPTXR remained reduced compared with baseline, and correlated with the clinical response to tofersen. Consistent with increasing CSF pleocytosis and intrathecal immunoglobulin production, inflammatory markers were significantly increased after 12 months of treatment. Interpretation Our results highlight a complex, time-dependent differential response of CSF biomarkers to tofersen treatment, and may pave the way for developing a panel of responsive proteins to make biomarker endpoints more robust in clinical trials for SOD1-ALS and beyond. ANN NEUROL 2025
Erstmals veröffentlicht: 9. August 2025
Gesehen am 30.10.2025